Molecular mechanisms and therapeutic strategies in overcoming chemotherapy resistance in cancer - Yixiang Gu; Ruifeng Yang; Yang Zhang; Miaomiao Guo; Kyle Takehiro; Ming Zhan; Linhua Yang; Hui Wang (Molecular Biomedicine)
Abstract Cancer remains a leading cause of mortality globally and a major health burden, with chemotherapy often serving as the primary therapeutic option for patients with advanced-stage disease, partially compensating for the limitations of non-curative treatments. However, the emergence of chemotherapy resistance significantly limits its efficacy, posing a major clinical challenge. Moreover, heterogeneity of resistance mechanisms across cancer types complicates the development of universally effective diagnostic and therapeutic approaches. Understanding the molecular mechanisms of chemoresistance and identifying strategies to overcome it are current research focal points. This review provides a comprehensive analysis of the key molecular mechanisms underlying chemotherapy resistance, including drug efflux, enhanced DNA damage repair (DDR), apoptosis evasion, epigenetic modifications, altered intracellular drug metabolism, and the role of cancer stem cells (CSCs). We also examine specific causes of resistance in major cancer types and highlight various molecular targets involved in resistance. Finally, we discuss current strategies aiming at overcoming chemotherapy resistance, such as combination therapies, targeted treatments, and novel drug delivery systems, while proposing future directions for research in this evolving field. By addressing these molecular barriers, this review lays a foundation for the development of more effective cancer therapies aimed at mitigating chemotherapy resistance.